La capilla de la nación florentina en Sevilla (1588-1765) - Rafael Japón (Mélanges de la Casa de Velázquez)
The large community of Tuscan merchants that had settled in Seville between the 16th and 17th centuries erected a place of common social representation: the chapel of the Florentine nation. This was located in the church of the convent of Santa María de Jesús and its decorative program fused cultural elements of their place of origin and of the city that welcomed them. However, the memory of this unique place in Spain was lost after a fire in 1765 and all traces of its existence have been lost until now.